Assessment of coronary risk, therapy adhesion and quality of life of hypertenses elderly - Natasha Teixeira Medeiros; Thereza Maria Magalhães Moreira (Universidade de Fortaleza, 2012)
Objective: Evaluate coronary risk, adherence and life quality of elderly patients with hypertension. Methods: Quantitative and analytical assessment, with a sample of 250 elderly hypertensive patients without co-morbidities, from a health unit of reference for specialized care in Fortaleza - CE, Brazil. We used a questionnaire evaluation of adherence to treatment of hypertension, coronary risk table, proposed by the American Heart Association and the WHOQOL-bref to assess the quality of life. Results: We found that 234 (93.6%) subjects presented non-compliance and 16 (6.4%), adherence; 122 (48.8%) had moderate coronary risk, 117 (46.8%) had potential risk and 11 (4.4%) had no risk. About the life quality, its average in the four areas was 14.57. Conclusion: The elderly hypertensive patients studied showed non-adherence to treatment, presence of coronary risk and variable average of life quality.